Policy Implementation Studies of the Tuberculosis Control Program Towards the Elimination of Tuberculosis in East Lombok Regency, West Nusa Tenggara Province - Ersandhi Resnhaleksmana; Maruni Wiwin Diarti; Ni Putu Karunia Ekayani; Yudha Anggit Jiwantoro; Iswari Pauzi (Lembaga Bale Literasi, 2026)
The NTB Provincial Health Office recorded that East Lombok Regency, with 35 Health Centers, had 7,331 suspected tuberculosis (TB) patients who received standard services, comprising 432 male cases (54.3%), 363 female cases (45.7%), totalling 795 cases, and 67 TB cases among children aged 0–14 years. The role of academics and stakeholders in implementing the 2020–2024 national TB control strategy is critically important. This study aimed to examine the implementation of the TB program control policy in East Lombok Regency. A qualitative approach was employed with 79 informants using in-depth interviews, group interviews, and FGDs. Informants included TB program managers at the district level, Health Office officials, health center staff, and TB patients. Six health centers were selected purposively: Terara and Masbagik Baru (high achievement), Lenek and Aikmel (medium achievement), and Selong and Lendang Nangka (low achievement). The study was conducted from August to October 2023. Results revealed that TB program control policy implementation has been carried out well, supported by community participation, cross-sector coordination, availability of facilities and funds, and communicative communication. However, local government funding ceased after COVID-19, hampering training, active case finding, and community counseling activities. Policy recommendations include reinstating local government funding and adding TCM (Tes Cepat Molekuler) tools and dedicated TB waiting and sampling rooms